Analisis Literasi Media Digital Ditinjau Dari Aspek Individual Competence Pada Guru Smk Sasmita Jaya Tangerang Selatan - Purwati Yuni Rahayu; Kusworo Kusworo; Heri Indra Gunawan (Faculty of training and education, Pamulang university, 2022)
ABSTRACTThe purpose of this study is to determine the teacher's understanding of digital media and to determine the level of individual competence of teachers at SMK Sasmita Jaya in digital media literacy. The approach used in this research is a quantitative approach with a survey methodology. Analysis of the data used in the form of descriptive statistics that describe the teacher's understanding of digital media and the level of individual competence. The results of the study found that the teacher's understanding of digital media literacy was in the medium category. The questionnaire instrument shows that the teachers of SMK Sasmita already have and are able to use the device actively and use it even >5 hours every day. However, this has not been used optimally in teaching and learning activities such as making teaching materials, learning media, and utilizing social media as a means of delivering information to students. Meanwhile, from the aspect of the category of Individual competence possessed by teachers, it has entered high. One aspect that becomes an important point is the teacher's ability to use the internet in his life. This also applies to a teacher who is a professional educator with competencies that must be possessed, one of which is adapting to technology.Keywords: Literacy; digital media; individual competence